2013
DOI: 10.1615/critrevimmunol.2013006618
|View full text |Cite
|
Sign up to set email alerts
|

Muller Glia in Retinal Innate Immunity: A Perspective on Their Roles in Endophthalmitis

Abstract: Müller cells are the predominant glial cell type in the retina and have a unique anatomy, with processes that span the entire retinal thickness. Although extensive morphological and physiological studies of Müller glia have been performed, much less is known about their role in retinal innate immunity, specifically in infectious endophthalmitis. They were found to express Toll-like receptors (TLRs), a major family of pattern recognition receptors (PRRs) that mediate innate responses and provide an important me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 117 publications
4
85
0
1
Order By: Relevance
“…The major protective mechanism that controls the influx of innate immune cells and pathogens into the posterior segment of the eye is the presence of BRB, consisting of the inner retinal vascular endothelial cells and outer RPE cells (40,41,47). Previous studies from our laboratory and others have shown that BRB dysfunction allows the entry of infectious agents into the retina/vitreous cavity and causes inflammation and tissue damage (48,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major protective mechanism that controls the influx of innate immune cells and pathogens into the posterior segment of the eye is the presence of BRB, consisting of the inner retinal vascular endothelial cells and outer RPE cells (40,41,47). Previous studies from our laboratory and others have shown that BRB dysfunction allows the entry of infectious agents into the retina/vitreous cavity and causes inflammation and tissue damage (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…As ZIKV was found to infect multiple retinal cell types and to induce the expression of multiple potential entry receptors, we next determined whether ZIKVinfected retinal cells elicit an innate immune response. TLRs have been shown to play an important role in orchestrating retinal innate responses in microbial infection (30,31,(38)(39)(40)(41), with TLR3 being implicated in viral infection. Our data showed that TLR3 mRNA expression was significantly upregulated in both ZIKVinfected Pr.…”
Section: Zikv Infects Multiple Retinal Cell Types and Induces Cell Dementioning
confidence: 99%
“…41,44 Like the aqueous humor, the vitreous humor that occupies the posterior chamber appears to exhibit similar anti-inflammatory properties, although these mechanisms are not clearly understood. 45 The blood-retinal barrier is also guarded by retinal pigment epithelial (RPE) cells, which form a layer between the retina and the vascular choroid. 41 These unique cells encompass a number of critical roles for maintaining retinal health, and also express death receptors like FASL and PD-L1 to lyse encroaching peripheral inflammatory cells, 42 and may even initiate inflammatory responses.…”
Section: Immune Privilege and Neurogliamentioning
confidence: 99%
“…8C, F, I). In the following statistical evaluation, we could not detect any statistically significant differences However, the eye is an immune privileged organ with a high level of transforming growth factor (TGF)-β2, contributing to the quiescence of microglia and Müller cells [30,42,43,45,46].…”
Section: Cre Recombinase Expression or Tamoxifen Treatment Do Not Altmentioning
confidence: 75%